2017
DOI: 10.12659/msm.904177
|View full text |Cite
|
Sign up to set email alerts
|

CLDN1 Increases Drug Resistance of Non-Small Cell Lung Cancer by Activating Autophagy via Up-Regulation of ULK1 Phosphorylation

Abstract: BackgroundThe aim of this study was to investigate the expression of CLDN1 in non-small cell lung cancer (NSCLC) and its mechanism of action in cisplatin resistance.Material/MethodsA total of 55 patients with NSCLC admitted to our hospital between October 2013 and October 2015 were included. NSCLC tissues and tumor-adjacent tissues (≥5 cm from tumor edge) were collected. Among the 55 patients, 37 had adenocarcinoma and 18 had squamous cell carcinoma. Quantitative real-time polymerase chain reaction was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 37 publications
(41 reference statements)
0
25
0
Order By: Relevance
“…Recently, it has been reported that the autophagosome marker Atg16L colocalizes with CLDN5 in endocytosed vesicles transported across the cells, indicating that the process of tight junction remodeling involves the regulation of autophagy [53]. Zhao Z. et al discovered that CLDN1 regulated drug resistance by promoting autophagy, which was mediated by ULK1 phosphorylation in non-small cell lung cancer [54]. In addition, J. Kim et al reported that CLDN1 functions as an autophagy stimulator to increase autophagy flux and accelerate the degradation of SQSTM1/p62 [55].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that the autophagosome marker Atg16L colocalizes with CLDN5 in endocytosed vesicles transported across the cells, indicating that the process of tight junction remodeling involves the regulation of autophagy [53]. Zhao Z. et al discovered that CLDN1 regulated drug resistance by promoting autophagy, which was mediated by ULK1 phosphorylation in non-small cell lung cancer [54]. In addition, J. Kim et al reported that CLDN1 functions as an autophagy stimulator to increase autophagy flux and accelerate the degradation of SQSTM1/p62 [55].…”
Section: Discussionmentioning
confidence: 99%
“…Another gene was CLDN1, which was upregulated more than 1.8-fold in both cell lines. CLDN1 is a member of the tight junction family of genes and has attracted attention because of its altered expression in many cancers as well as its association with cellular properties (invasion, migration) indicating cancer progression, which are normalized upon its knockdown in breast and lung cancer cells 45,46 . Further, PRMT6 was downregulated more than 1.7-fold in both cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that overexpression of ULK1 is inversely related to the prognosis of various tumors, such as colon cancer, breast cancer, lung cancer, nasopharyngeal cancer, and esophageal cancer [136]. The knockdown of ULK1 in NSCLC cells induces an increase in apoptosis and makes them more sensitive to cisplatin [209]. SBI0206965, a selective inhibitor of ULK1, can significantly reduce the cell survival of cisplatin-resistant NSCLC cells by decreasing the conversion of LC3 I to LC3 II, upregulating the expression of autophagy substrate P62, and inhibiting the progress of autophagy.…”
Section: Small Molecule Drugs Targeting Ulk Reverse Tumor Resistancementioning
confidence: 99%